Effect of intraoperative dexmedetomidine on hepatic ischemia-reperfusion injury in pediatric living-related liver transplantation: A propensity score matching analysis - Zhang, Liang; Cui, Ling-Li; Yang, Wen-He; Xue, Fu-Shan; Zhu, Zhi-Jun (Frontiers in Surgery, 2022)
Background: Hepatic ischemia-reperfusion injury (HIRI) is largely unavoidable during liver transplantation (LT). Dexmedetomidine (DEX), an α2-adrenergic agonist, exerts a variety of organ-protective effects in pediatric populations. However, evidence remains relatively limited about its hepatoprotective effects in pediatric living-related LT. Methods: A total of 121 pediatric patients undergoing living-related LT from June 2015 to December 2018 in our hospital were enrolled. They were classified into DEX or non-DEX groups according to whether an infusion of DEX was initiated from incision to the end of surgery. Primary outcomes were postoperative liver graft function and the severity of HIRI. Multivariate logistic regression and propensity score matching (PSM) analyses were performed to identify any association. Results: A 1:1 matching yielded 35 well-balanced pairs. Before matching, no significant difference was found in baseline characteristics between groups except for warm ischemia time, which was longer in the non-DEX group (44 [38–50] vs. 40 [37–44] min, p = 0.017). After matching, the postoperative peak lactic dehydrogenase levels decreased significantly in the DEX group than in the non-DEX group (622 [516–909] vs. 970 [648–1490] IU/L, p = 0.002). Although there was no statistical significance, a tendency toward a decrease in moderate-to-extreme HIRI rate was noted in the DEX group compared to the non-DEX group (68.6 % vs. 82.9 %, p = 0.163). Patients in the DEX group also received a significantly larger dosage of epinephrine as postreperfusion syndrome (PRS) treatment (0.28 [0.17–0.32] vs. 0.17 [0.06–0.30] μg/kg, p = 0.010). However, there were no significant differences between groups in PRS and acute kidney injury incidences, mechanical ventilation duration, intensive care unit, and hospital lengths of stay. Multivariate analysis revealed a larger graft-to-recipient weight ratio (odds ratio [OR] 2.657, 95% confidence interval [CI] 1.132–6.239, p = 0.025) and intraoperative DEX administration (OR 0.333, 95% CI 0.130–0.851, p = 0.022) to be independent predictors of moderate-to-extreme HIRI. Conclusion: This study demonstrated that intraoperative DEX could potentially decrease the risk of HIRI but was associated with a significant increase in epinephrine requirement for PRS in pediatric living-related LT. Further studies, including randomized controlled studies, are warranted to provide more robust evidence.